The amazing adventures of Aaron Broom [large type] : a novel - Hotchner, A. E. (Wheeler Publishing, a part of Gale, a Cengage Company, 2018)
"Street-savvy, almost-thirteen-year-old Aaron Broom is guarding his father's car when he witnesses a robbery gone wrong in a jewelry store across the street. To Aaron's shock, his father, a traveling watch salesman in the wrong place at the wrong time, is fingered as the prime suspect in the murder. Despite seeing the real killer flee the scene, Aaron can't do much to help in the moment--no one will take a kid's word for it. Undaunted, Aaron enlists an unlikely band of friends and helpful adults to clear his father's name."--